PERLINDUNGAN HUKUM PENCIPTA LAGU YANG KARYANYA DIPAKAI DI APLIKASI TIKTOK - Kristianto Oktavian Saragih (INSANI: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Abtract Some song copyright violations on the TikTok platform such as uploading songs and rearrangements without permission or commercialized, will clearly harm the songwriter. because with commercial use without permission, the creator automatically does not get economic rights or royalties from the platform. The purpose of the study is to know and understand how the responsibility of the TikTok platform for violations of song copyrights in the TikTok application, as well as to know and understand the legal protection of songwriters for illegal commercialization of their copyrights in the TikTok application. The method used in this paper is Normative Juridical, Conclusion; the creator can file a lawsuit for material claims, restoration of the original state, prohibition of acts, as well as complaints that can result in compensation and fines for violators. preventive protection of the creator's copyright is still ineffective because TikTok does not support legal protection and government supervision. Therefore, repressive measures are needed to enforce liability in accordance with applicable laws. Keywords : TikTok App, Copyright, Legal Protection Abstrak Beberapa pelanggaran-pelanggaran Hak Cipta lagu yang ada di platform TikTok seperti mengunggah lagu dan aransemen ulang tanpa izin atau dikomersialkan, maka jelas akan merugikan si pencipta lagu. karena dengan penggunaan secara komersial tanpa izin, otomatis si pencipta tidak mendapatkan hak ekonomi atau royality dari platform tersebut. Tujuan penelitian Untuk mengetahui dan memahami bagaimana tanggung jawab dari pihak platform TikTok terhadap pelanggaran Hak Cipta lagu pada aplikasi Tiktok, jugaUntuk mengetahui dan memahami perlindungan hukum terhadap pencipta lagu atas komersialisasi Hak Ciptanya secara illegal pada aplikasi TikTok.Metode yang digunakan pada tulisan ini adalah Yuridis Normatif, Kesimpulan; pencipta dapat mengajukan gugatan untuk tuntutan materi, pemulihan keadaan semula, larangan perbuatan, serta delik aduan yang dapat mengakibatkan ganti rugi dan sanksi denda bagi pelanggar. perlindungan preventif hak cipta pencipta masih kurang efektif karena TikTok tidak mendukung perlindungan hukum dan pengawasan pemerintah. Oleh karena itu, diperlukan langkah represif untuk menegakkan pertanggungjawaban sesuai undang-undang yang berlaku.